Enhanced nitrate removal from surface water in a denitrifying woodchip bioreactor with a heterotrophic nitrifying and aerobic denitrifying fungus. (May 2020) - Yao, Zongbao; Yang, Liu; Wang, Fang; Tian, Linqi; Song, Na; Jiang, Helong
Highlights: Penicillium tropicum strain IS0293 was isolated from surface water and identified. The strain IS0293 can remove NO3 − using variety of organic carbon substances. Nitrate and TOC removal in a DWB was enhanced by strain IS0293 inoculation. The strain showed capacity for prolonging the stable operation time of DWB. Abstract: A heterotrophic nitrifying and aerobic denitrifying fungus was isolated from lake water and identified as Penicillium tropicum strain IS0293. The strain exhibited efficient heterotrophic nitrification-aerobic denitrification ability and could utilize ammonium, nitrite and nitrate as a sole nitrogen source. Batch tests demonstrated that strain IS0293 can remove nitrate using variety of organic carbon compounds as carbon sources. The effect of woodchip leachate collected at different degradation times on denitrification performance of the strain was also investigated. Furthermore, two denitrifying woodchip bioreactors were constructed to assess the bioaugmention of strain IS0293 for nitrate removal from surface water. Results demonstrated that the incubation of strain IS0293 enhanced the nitrate removal efficiency of the bioreactor. In addition, the average effluent TOC content of the bioaugmention bioreactor was 38.22% lower than the control bioreactor. This study would be valuable to develop an effective technology for nitrate-laden surface water under aerobic conditions.